2021
DOI: 10.1111/tmi.13563
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and predictors of mortality in patients with melioidosis: the Kapit experience

Abstract: objectives Melioidosis, caused by Burkholderia pseudomallei, is prevalent in rural areas of Malaysia. The aim of this study is to delineate the epidemiology and predictors of mortality from melioidosis in Kapit district, Sarawak.methods For this retrospective study of patients with culture-confirmed melioidosis admitted to Kapit Hospital, Sarawak, Malaysia, between July 2016 and July 2019, epidemiological, clinical and microbiological data were obtained. Univariate and multivariate logistic regression analyses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 23 publications
2
5
0
Order By: Relevance
“…Nevertheless, all gentamicin-susceptible isolates that were analyzed were confirmed to possess a single-nucleotide polymorphism mutation in the amrB gene through a previously published AS-PCR assay, inferring that these isolates may in fact belong to ST881 or ST997. In a recent melioidosis study in Kapit, another rural district located in central Sarawak ( Figure 1 ), 92% of infections were due to gentamicin-susceptible isolates, consistent with the findings in the rural areas in our study [ 11 ]. In other melioidosis-endemic regions in Australia, Asia, and SEA, including peninsular Malaysia, studies of clinical Bp isolates have demonstrated usually high levels of strain diversity [ 12–16 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Nevertheless, all gentamicin-susceptible isolates that were analyzed were confirmed to possess a single-nucleotide polymorphism mutation in the amrB gene through a previously published AS-PCR assay, inferring that these isolates may in fact belong to ST881 or ST997. In a recent melioidosis study in Kapit, another rural district located in central Sarawak ( Figure 1 ), 92% of infections were due to gentamicin-susceptible isolates, consistent with the findings in the rural areas in our study [ 11 ]. In other melioidosis-endemic regions in Australia, Asia, and SEA, including peninsular Malaysia, studies of clinical Bp isolates have demonstrated usually high levels of strain diversity [ 12–16 ].…”
Section: Discussionsupporting
confidence: 91%
“…The rate of diabetes was consistent with other studies [ 31 ] but was significantly lower in those infected with gentamicin-susceptible Bp at 42%. In the recent melioidosis study in Kapit, the absence of risk factors was reported in nearly 50% of cases [ 11 ], a figure substantially higher than described in most other studies [ 31 ]. The lower rate of diabetes and the higher proportion without identified risk factors in those infected with gentamicin-susceptible Bp may in part reflect the rural population that accounted for the vast majority of these cases, with a higher exposure burden to environmental Bp in the rural areas.…”
Section: Discussionmentioning
confidence: 88%
“…In contrast, lower mortality rates of 14% and 21% were reported in Australia [ 12 , 57 ]. In Malaysia, various mortality rates have been reported in different states, ranging from 12% to 65% [ 3 , 5 , 7 , 11 , 20 , 21 , 22 , 23 , 24 , 51 ]. Recently, the lowest mortality rate (6%) ever documented was recorded in Darwin, Australia in a 30-year study period due to the application of an intensivist-led model of care and the empirical prescription of meropenem for critically ill patients [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Over the last few decades, a number of epidemiological studies have been reported showing demographics, clinical spectrum, prognosis, and laboratory and antibiotic susceptibility testing (AST) findings in melioidosis patients to facilitate accurate clinical diagnosis and treatment. However, the information is restricted to specific locations within Malaysia [ 5 , 11 , 20 , 21 , 22 , 23 , 24 ]. Sabah is one of 13 states in Malaysia and is located on the island of Borneo.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, however, head and neck infections are rarely reported in children in northern Australia [ 6 , 9 ]. In adults, head and neck melioidosis is uncommon [ 29 , 30 ]. The high prevalence of head or neck infections among children in Southeast Asia is thought to be related to acquisition of B. pseudomallei through the oral/nasal mucosa or conjunctiva, possibly via exposure to contaminated water sources, as opposed to inhalation and ingestion postulated in adults with pneumonia or bacteraemia and skin inoculation among children in northern Australia [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%